Clinical analysis of Hem-o-lok closure of the left subclavian artery stump in acute Stanford type A aortic dissection - Li, Jian-Qiang; Sha, Tu-Min; Dong, Ping; Li, Xiao-Xia; Zhang, Peng; Zhao, Zhen-Qing; Jie, Lin-lin; Zha, Lei; Liu, Chao-Liang (Frontiers in Cardiovascular Medicine, 2024)
ObjectiveThis study aims to summarize the clinical experience of using Hem-o-lok clips for the closure of the left subclavian artery (LSA) stump in patients with acute Stanford type A aortic dissection.MethodsClinical data were collected from 96 patients with acute type A aortic dissection admitted to our hospital from January 2020 to December 2022. The cohort comprised 61 males and 35 females, with an average age of 52 ± 9.57 years and a mean body weight of 79.54 ± 12.57 kg. The mean diameter of the LSA opening was 11.24 ± 1.48 mm, as measured by computer tomography angiography (CTA) of the thoracoabdominal aorta. All patients underwent emergency Sun's procedure. The surgical method for the LSA stump was selected based on the anatomical location, depth of the subclavian artery, vessel diameter, length of the free vessel, and extent of dissection. Techniques included the use of two Hem-o-lok clips, 5–0 prolene suture with one Hem-o-lok clip, and 5–0 prolene suture alone.ResultsAll the patients successfully completed Sun's procedure as planned. Two Hem-o-lok clips were used to close the stump of the LSA in 38 cases. A combination of 5–0 prolene suture and one Hem-o-lok clip were used to close the stump of the LSA in 54 cases. The LSA stumps for 4 cases were closed with 5–0 prolene suture only. Postoperative complications included cerebral infarction in one patient, renal insufficiency in one patient, and gastrointestinal bleeding in one patient. There were no surgery-related deaths, no paraplegia,and all patients were successfully discharged. The 1-year follow-up CTA of the thoracoabdominal aorta demonstrated effective thrombosis of the false lumen in the stented segment of the thoracic aorta, no aneurysmal dilatation, and successful closure of the LSA stump.ConclusionsThe simplified approach of Hem-o-lok closure of the LSA stump largely mitigates the difficulty in the LSA operation process,shortens the time of operation and reduces bleeding risk, thus effectively improving a patient's prognosis and yielding satisfactory clinical outcomes.